Non-Tariff Measures: Data and Quantitative Tools of Analysis - Alessandro Nicita; Jaime de Melo (Fondation pour les études et recherches sur le développement international (FERDI), 2018)
This paper provides a tour d'horizon on where we stand with the information, and analysis of Non-Tariff Measures (NTMs). The analysis of NTMs has been fragmentary, not keeping pace with their increasing prevalence and their increasing complexity. Capturing and classifying these NTMs is still a daunting task because of the data limitations identified in this paper: comprehensiveness, diversification, lack of precision, dimensionality, time dimension (NTMs are rarely available for several years which makes it difficult to control for confounding factors). Most NTM data inventories are registered on a binary basis restricting the use of descriptive statistics to a few indices. Disentangling precautionary from protectionist motives of NTMs is difficult as the presence and/or intensity of NTMs is likely to depend on import volumes. Quantity-based and price-based approaches to estimate AVEs are discussed along with methods to measure distortionary costs of NTMs. Examples of 'top down' and 'bottom up' approaches are shown to reveal some stylized patterns. Among these, trade costs have been falling around the world, but low-income countries are not catching up, for reasons likely to include the uneven effects of reductions in transport costs and the greater cost-raising effects of technical barriers to trade for low-income countries. For all income groups, the average trade restrictiveness of NTMs is estimated to be higher than the average restrictiveness of tariffs and the average restrictiveness of NTMs is estimated to be higher for low-income countries.
Keywords: 330; Non-tariff measures